2022
DOI: 10.1039/d1ma01052b
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared absorbing aza-BODIPYs with 1,7-di-tert-butyl groups by low-barrier rotation for photothermal application

Abstract: Near-infrared absorbing aza-BODIPYs with the 1,7-Di-tert-butyl groups (tBuazaBDP) were successfully synthesized for the first time. By X-ray crystal analysis, S-tBuazaBDP is more twisted than the reported dye tetraphenyl aza-BODIPY. tBuazaBDPs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The molar extinction coefficients increase slightly, along with the change of the pull or push electron groups. Especially, we were surprised to discover that the introduction of the –SMe group led to low fluorescence quantum yield ( Φ f ​= ​0.05), compared with other tBuazaBDP s. In sharp contrast to Rev-SMe-tBuazaBDP [ 52 ] with the group exchange at 1,7 and 3,5-sites ( Scheme 1 b) from SMe-tBuazaBDP , although the maxima emission between Rev-SMe-tBuazaBDP (λ em ​= ​713 ​nm) and SMe-tBuazaBDP (λ em ​= ​708 ​nm) could indeed be comparable, the maximum absorption of SMe-tBuazaBDP (λ abs ​= ​602 ​nm) is obviously hypochromatic shift relative to that (λ abs ​= ​666 ​nm) of Rev-SMe-tBuazaBDP , so SMe-tBuazaBDP shows a larger Stokes shift (106 ​nm) than that (47 ​nm) of Rev-SMe-tBuazaBDP . Therefore, a breakthrough of ultra-large Stokes shift was found in the spectral properties of 3,5-di- tert -butyl-substituted aza-BODIPYs in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The molar extinction coefficients increase slightly, along with the change of the pull or push electron groups. Especially, we were surprised to discover that the introduction of the –SMe group led to low fluorescence quantum yield ( Φ f ​= ​0.05), compared with other tBuazaBDP s. In sharp contrast to Rev-SMe-tBuazaBDP [ 52 ] with the group exchange at 1,7 and 3,5-sites ( Scheme 1 b) from SMe-tBuazaBDP , although the maxima emission between Rev-SMe-tBuazaBDP (λ em ​= ​713 ​nm) and SMe-tBuazaBDP (λ em ​= ​708 ​nm) could indeed be comparable, the maximum absorption of SMe-tBuazaBDP (λ abs ​= ​602 ​nm) is obviously hypochromatic shift relative to that (λ abs ​= ​666 ​nm) of Rev-SMe-tBuazaBDP , so SMe-tBuazaBDP shows a larger Stokes shift (106 ​nm) than that (47 ​nm) of Rev-SMe-tBuazaBDP . Therefore, a breakthrough of ultra-large Stokes shift was found in the spectral properties of 3,5-di- tert -butyl-substituted aza-BODIPYs in this work.…”
Section: Resultsmentioning
confidence: 99%
“…To take advantage of this molecular design model, further molecular regulation was done to skillfully construct 1,7-di- tert -butyl aza-BODIPYs. 81 The molecular scaffolds, including diphenyl, alkyl-fused cyclic diphenyl, and methylsulfuryl phenyl substitutions, were prepared (Fig. 5a).…”
Section: Non-aryl-substituted Aza-bodipys At 17-sitesmentioning
confidence: 99%
“…23 Very recently, Jiang et al reported 1,7-di- tert -butyl-substituted aza-BODIPYs by low-barrier rotation to enhance the photothermal effect. 24,25 Börjesson et al also reported 1,7-di- sec -butyl-substituted aza-BODIPYs by Suzuki coupling. 26 However, 3-ethyl-2,4-dimethylpyrrole was employed to challenge the generation of aza-BODIPY with the methyl groups at 3,5-sites, but provided 3-amino/3-acetamido BODIPY (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1a). [23][24][25][26] O'Shea et al reported 1,7-dimethyl substituted aza-BODIPY, which exhibited excellent NIR emission with high fluorescence quantum yield (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%